Efficacy of Macro and Micronutrient Interventions in Adolescent Nutritional Status: A Systematic Review - Sulfianti; Lina Fitriani; Hasnidar; Mustar; Damai Yanti (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The authors conducted a systematic review of adolescents receiving a macronutrient (iron, zinc) intervention compared to a multi-micronutrient intervention to investigate their efficacy on nutritional status. Systematic searches were conducted in four database sources—Science Direct, ProQuest, EBSCO, and Google Scholar. A PICO worksheet was used to define keywords, including 1) Patient/Problem: Preconception for adolescent OR girl student, 2) Intervention: Iron and zinc OR Fe and Zn OR macronutrients, 3) Comparison: Multi-micronutrient, and 4) Outcome: Nutritional status. Inclusion criteria included female adolescents aged 9–24 years and English and Indonesian articles published from 2013 to 2020. The risk of bias was assessed by minimizing four potential sources of bias: sample selection, research design, control of confounding variables, and data collection techniques. Result: 10 relevant studies discussing iron, zinc, and multi-micronutrient supplements for adolescents were identified. Iron and zinc interventions are efficacious in preventing anemia, enhancing hemoglobin concentration, improving body mass index, and reducing the risk of low birth weight and preeclampsia for women in the preconception phase. The multi-micronutrient intervention has similar efficacy, but it can better affect the maternal immune response and the production of the human placental lactogen hormone, which ultimately increases placental weight and birth weight while lowering the risk of abortion and prematurity. Conclusion: Iron, zinc, and multi-micronutrient interventions play a pivotal role in improving the nutritional status of adolescents in preparing the preconception phase because they provide positive benefits and can prevent nutritional deficiencies before pregnancy, during pregnancy, and after delivery.